Immunogenic HIV variant peptides that bind to HLA-B8 can fail to stimulate cytotoxic T lymphocyte responses. - McAdam, S; Klenerman, P; Tussey, L; Rowland-Jones, S; Lalloo, D; Phillips, R; Edwards, A; Giangrande, P; Brown, A; Gotch, F (1995)
Cytotoxic T lymphocyte responses in HIV infection can be impaired through variation in the epitope regions of viral proteins such as a gag. We report here an analysis of variant epitope peptides in three gag epitopes presented by HLA B8. Fifteen variant peptides were examined for their binding to HLA-B8; all but one bound at concentrations comparable to known epitopes. All except two of those that bound could be recognized by CTL from an HLA-B8 positive HIV-1-infected patient and were therefore immunogenic. However, in a hemophiliac patient studied in detail, there was a failure to respond to two immunogenic peptide epitopes representing virus present as provirus in the patient's peripheral blood. In one case, the patient's CTL had previously responded to the peptide; in the other case, there was a good response to a peptide of closely related sequence. Thus there was a selective failure of the CTL response to some proviral epitopes. This impaired reaction to new variants could contribute to the loss of immune control of the infection.